Introduction in Optimization of Open Electrical Circuits for Dicrete Parameters - М. I. Fursanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An efficient methodology, a structural algorithm and a computer program for detection of optimum state of open electrical circuits for discrete parameters have been developed in the paper. The methodology is based on investigation of the total cost elasticity matrix for discrete optimized parameters. The efficiency of the developed structural algorithm is proved by numerical examples. The paper shows that losses in under-loaded electrical circuits can be by two- and even more fold decrease due to setting of optimum nominal transformer capacitance.